New Developments in Tissue Engineering and Regeneration - Fernandes, Paulo Rui.; da Silva Bartolo, Paulo Jorge; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume presents a new contribution for the field of Tissue Engineering with a focus on the development of mathematical and computational methods that are relevant to understand human tissues, as well to model, design, and fabricate optimized and smart scaffolds. The multidisciplinary character of this field has motivated contributions from different areas with a common objective to replace damaged tissues and organs by healthy ones. This work treats tissue healing approaches, mathematic modelling for scaffold design and bio fabrication methods, giving the reader a broad view of the state of the art in Tissue Engineering. The present book contains contributions from recognized researchers in the field, who were keynote speakers in the Fourth International Conference on Tissue Engineering, held in Lisbon in 2015, and covering different aspects of Tissue Engineering. The book is strongly connected with the conference series of ECCOMAS Thematic Conferences on TissueEngineering, an event that brings together a considerable number of researchers from all over the world, representing several fields of study related to Tissue Engineering.
Preface -- Computational modelling of wound healing: Insights to develop new treatments, by M.J. Gomez-Benito, C. Valero, J.M. García-Aznar and E. Javierre -- Traction force microscopy in differentiating cells, by Shada Abuhattum, Amit Gefen, and Daphne Weihs -- Adaptive Multi-resolution Volumetric Modeling of Bone Micro-Structure, by Yizhak Ben-Shabat, Anath Fischer -- Low temperature 3D printing of drug loaded bioceramic scaffolds and implants, by Susanne Meininger, Elke Vorndran, Miguel Castilho, Paulo R. Fernandes, Uwe Gbureck -- A biomechanical approach for bone regeneration inside scaffolds embedded with BMP-2, by Carolina Gorriz, Frederico Ribeiro, José Miranda Guedes, João Folgado, Paulo R. Fernandes.
Keywords: Biomedical engineering; Biomaterials; Medicine -- Research; Biology -- Research; Biomedical Engineering and Bioengineering; Biomaterials; Biomedical Research